THE SPECIFICS OF ADAPTATION AND INTERNAL DISORDER PATTERN OF ADULTS WITH DISABILITIES - Adeeva, T.N.; Tichonova, I. V. (Modern Psychology, 2021)
The internal disorder pattern is considered as a component of the Self-concept and is understood as a complex of sensations, knowledge, experiences, and motivational changes associated with the disorder. This phenomenon includes four components: physical, cognitive, emotional, and motivational. The features of the internal disorder pattern of adults with disabilities (IPD) are defined in the study. The phenomenon of IPD is considered as a factor in the formation of the Self-concept, which means that it can be associated with a person’s attitude to himself, to others, with the motives of activity, with the formation of various personality traits. The components of IPD have different contents and severity depending on the variant of dysontogenesis.The greatest severity of the components of IPD is observed in groups of adults with impaired functions of the musculoskeletal system and hearing disorders. The internal pattern of the disorder is important for the socio-psychological adaptation of the individual. The study determined the relationship of IPD with such indicators of adaptation as emotional comfort, external and internal control, dominance, and avoidance of problems. Some of the IDP parameters are predictors of adaptation parameters for various variants of impaired development.